(untitled) (World Bulletin of Social Sciences, 2024)
This article discusses linguistic problems of translation, written and oral translation, interlingual differences and translation (terms of kinship), linguistic and non-linguistic problems of translation, comparative grammar and comparative methodology, gender category in translation, types and types of translation, areas and genres are discussed. talk about lines